Successful treatment of Candida albicans endocarditis in a child with leukemia--a case report and review of the literature - Ariffin, H.; Ariffin, W.; Tharam, S.; Omar, A.; de Bruyne, J.; Lin, H.P. (Stamford Publishing Pte Ltd / Singapore Medical Association, 1999)
Candida species is now being increasingly recognised as an important cause of endocarditis especially in immunocompromised patients. A case of Candida albicans endocarditis in a child with acute lymphoblastic leukemia (ALL) is reported. The child did not have a central venous catheter at any time. Treatment consisted of intravenous amphotericin B and fluconazole for 3 weeks followed by oral fluconazole for 2 weeks. No surgical resection was necessary. We highlight here the importance of echocardiography in the management of prolonged febrile neutropenia and discuss the dilemma of continuing chemotherapy in such patients.